Factor Related With the Anemia Incidence Of Adolescent Girl in Private High School Santa Lusia Medan, 2019 - Risda Mariana Manik; Hetty Gustina Simamora (Universitas Andalas, 2019)
According to data Basic Healt Research (Riskesdas) in 2016, as many as 22,7% women of reproductive age more than 15 years indicate anemia. Anemia that often occurs is iron deficiency anemia, the incidence reaches 50% of the total anemia. There is a significant relationship between nutritional status and incidence of anemia in adolescent.This study was an observational analytic with a cross sectional approach. This study was conducted in private high school Santa Lusia Medan. The population of this study were adolescent girl with a total sample 74 using total sampling technique. The research material in the form scales and height measurements to measure boddy mass index, quesioner for iron consumption patterns and consumption habits of Fe tablet and hemoglobin levels were examined using haemometer digital. Data analysis used chi square test (α=0,005).The results of the research are variabels related to anemia incidence are body mass index (sig=0,019), iron consumption patterns (sig=0,017), Fe tablet consumption habit (sig=0,045). Conclusion this study is factor causing anemia in adolescent girls is the pattern of iron consumption. Adolescent girl who have irreguler iron consumption pattern have an oppurtunity to experience anemia of 4,250 compared to adolescent girl who have reguler iron consumption patterns.